New genus of Megalopsalidinae (Arachnida: Opiliones: Monoscutidae) from north-eastern Australia - Taylor, Christopher K.; Hunt, Glenn S. (Zootaxa, 2009)
Neopantopsalis n. gen. represents a previously unrecognised radiation of Opiliones from Queensland and northern New South Wales. Neopantopsalis quasimodo n. sp. is described from specimens examined but never published by the late G. S. Hunt. N. pentheter n. sp., N. psile n. sp. and N. thaumatopoios n. sp. are also described, while Pantopsalis continentalis and Spinicrus camelus are recombined as N. continentalis n. comb. and N. camelus n. comb., respectively. Neopantopsalis is distinguished from other genera of Monoscutidae by humps on the dorsal prosomal plate, lengthened spine rows on leg I, reduced bristle groups on the penis, and a long, dorsoventrally flattened glans. Male dimorphism is postulated for N. quasimodo, N. pentheter and N. psile, with rarer minor males that are considerably smaller and have less developed secondary sexual characteristics than the more common major males. A new terminology is introduced to facilitate descriptions of the propeltidium of Megalopsalidinae.